Model Pendidikan Akhlak dalam Kitab Nashoihul Ibad Karya Syeikh Imam Nawawi Al-bantani - Sya’diyah, Siti Aminatus; Fauzi, Ahmad; Maghfiroh, Ummi Lailia (Jurnal Keislaman, 2024)
The importance of developing moral education which includes holistic and sustainable aspects has highlighted attention to the moral education model. The book "Nashoihul Ibad" written by Sheikh Imam Nawawi Al-bantani is widely recognized as one of the main references in efforts to enrich Islamic morals. This research aims to conduct an analysis of the moral education model contained in the book "Nashoihul Ibad". The research method uses library research. The research results explain that moral education in the Nashoihul Ibad book consists of three models: First, moral education by instilling awareness about divinity and its relationship with humans. Second, moral education through the formation of noble attitudes and behavior and relationships with fellow humans. Third, moral education further develops personal qualities including fortitude, honesty, courage and responsibility in a social context.